2015
DOI: 10.1002/pip.2588
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of 15% efficient CIGSSe solar cells from nanoparticle inks

Abstract: We report a total-area power conversion efficiency of 15% for a copper indium gallium disulfoselenide (CIGSSe) solar cell fabricated from a copper indium gallium disulfide (CIGS) nanoparticle ink based process. Careful optimization of the fabrication process has resulted in a significant improvement in efficiency compared to our previously reported efficiency of 12%. This efficiency ranks among the highest reported in the literature for solution processed CIGSSe. Despite having an absorber thickness of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
123
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 33 publications
0
123
0
Order By: Relevance
“…[11][12][13][14][15] This often acts as a bottleneck in the use of these NCs for photoactive applications. Typically, multinary metal chalcogenides possess many desirable attributes, such as high absorption coefficient and high photo-stability for optoelectronic applications, [16][17][18][19][20][21] and a record power conversion efficiency of 21.7% has been obtained in the bulk form following physical deposition techniques, 22 which is close to the efficiency of polycrystalline silicon solar cells. But, when it comes to nanoscale, the presence of multiple trap states and the lack of the knowledge about their ultrafast carrier trapping dynamics limit their efficiency in device-based applications.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] This often acts as a bottleneck in the use of these NCs for photoactive applications. Typically, multinary metal chalcogenides possess many desirable attributes, such as high absorption coefficient and high photo-stability for optoelectronic applications, [16][17][18][19][20][21] and a record power conversion efficiency of 21.7% has been obtained in the bulk form following physical deposition techniques, 22 which is close to the efficiency of polycrystalline silicon solar cells. But, when it comes to nanoscale, the presence of multiple trap states and the lack of the knowledge about their ultrafast carrier trapping dynamics limit their efficiency in device-based applications.…”
mentioning
confidence: 99%
“…18 Recently, the nanoparticle-ink-based process proved its potential by showing a very high solar cell efficiency of 15%, based on a Mo back contact. 19 In this study, we demonstrated the effectiveness of a nanocrystal-ink-based CIGSSe solar cell on a transparent and conductive oxide (e.g., fluorine-doped SnO 2 , FTO)coated glass substrate. As a reference, the same CIGSSe absorber film was also synthesized on typical Mo-coated glass, and the morphologies, crystal structures, and compositional distributions of the CIGSSe films were investigated.…”
Section: Introductionmentioning
confidence: 83%
“…After sintering of the as‐prepared film, the nanoparticles are changed to uniform films of large grain size and high crystallinity . Recently, the nanoparticle‐ink‐based process proved its potential by showing a very high solar cell efficiency of 15%, based on a Mo back contact …”
Section: Introductionmentioning
confidence: 90%
“…The CIGS deposition by nonvacuum process offers potential advantages over vacuum processing, such as 1) uniform deposition over large area of the substrate; 2) high materials utilization; and 3) low‐cost process . Recently, several solution‐based approaches with precursor solutions, nanoparticle‐based inks, organometallic compounds, and metal alloys have been demonstrated for CIGS thin‐film solar cell fabrication with high conversion efficiencies of up to ≈16% . The photovoltaic efficiency gap between vacuum and nonvacuum processed CIGS films has been reduced in last few years thus showing promise for commercialization …”
Section: Introductionmentioning
confidence: 99%
“…[3,5,6] Recently, several solutionbased approaches with precursor solutions, nanoparticle-based inks, organometallic compounds, and metal alloys have been demonstrated for CIGS thin-film solar cell fabrication with high conversion efficiencies of up to %16%. [7][8][9][10] The photovoltaic efficiency gap between vacuum and nonvacuum processed CIGS films has been reduced in last few years thus showing promise for commercialization. [11][12][13][14] The tuning of the chemical composition of the CIGSe nanoparticles optimizes the conversion efficiency as the optical and electrical properties of the absorber layers strongly depend on the chemical stoichiometries of Cu-In-Ga-Se.…”
Section: Introductionmentioning
confidence: 99%